A primer in public policy analysis: techniques and methods - Eissa, Garoot Suleiman; Ambali, Abdul Raufu (IIUM Press, 2012)
This text is an introductory concise text prepared for advanced undergraduates. The main purpose is to simplify as much as possible a field of knowledge that is judged as difficult requiring much preparation in economics and quantitative methods. The main texts in this field are generally considered as difficult by the students at this level of instruction. The present text discusses the most central issues in policy analysis in simple terms and reviews the basic techniques employed to guide analysis. However, the book may also prove useful in another dimension: the use of local examples and cases in addition to the authors’ own examples which serve as easier examples for the students to comprehend. The main texts such as Dunn (1994) or Weimer and Vining (1999) are addressed to American readers and use American examples throughout. The second is almost a text book in welfare economics which we usually teach to postgraduates but is also required at the undergraduate level. The first chapter of this book defines, rationalizes and explains public policy as well as the practice of public policy analysis. The second chapter discusses issues relevant as a useful background to policy analysis: the policy making process and the place of policy analysis in it, policy analysis as welfare economics, policy analysis as rational choice and, finally, policy analysis as political decision making. The authors are of the opinion that policy analysis is a combination of all of these approaches. Chapter three is the first chapter pertaining to the analysis process; it handles problem analysis: problem identification, problem definition, problem structuring and problem modeling. While the fourth chapter seeks to explain the techniques and methods of forecasting, which are classified under quantitative or qualitative techniques. Forecasting is central to policy analysis because consequences of policies, aimed at resolution of social problems, take place in the future; hence it is important to speculate about the future. Chapter five pertains to analysis of alternatives and policy recommendation using political, economic, technical, administrative and social feasibilities. This chapter includes some hints pertaining to Islamization of public policy and suggesting that the approach of public policy as policy argument can be developed to derive principles for Islamization. Whereas chapter six exposes methods of evaluation of policy impacts to disclose the real impact of policy as objectively as possible. It is needless to indicate that this constitutes the final stage of policy analysis. Chapters seven and eight come in the form of applications of some of the ideas displayed in the book to real world policies with special focus on the Malaysian context. It is largely based on the authors’ experiences and research. Chapter seven involves two case studies where concepts of Islamization of public policy find real applications. In the first case attempt is made to discuss policies of privatization in light of Islamic principles and traditions. While the second case combines Islamic principles and rational analysis of cause and effect to analyse Malaysia’s policies for environmental protection. The final chapter uses straightforward main stream analysis of policy approach to evaluate Malaysia’s policies for the preservation of natural resources which uses stages of analysis of the policy process to expose policy. This text can also be used by students at other local universities and can be used by postgraduate students to accompany other text books as it might prove to be helpful. We hope that this concise book will prove to be useful as a simplified introductory book in public policy analysis the serves well the objectives envisioned.